2006
DOI: 10.1158/0008-5472.can-05-3058
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to Imatinib of Bcr/Abl P190 Lymphoblastic Leukemia Cells

Abstract: Around 20% of patients with acute lymphoblastic leukemia are Philadelphia chromosome positive (Ph-positive acute lymphoblastic leukemia) and express the Bcr/Abl tyrosine kinase. Treatment with the tyrosine kinase inhibitor Imatinib is currently standard for chronic myelogenous leukemia, which is also caused by Bcr/Abl. However, Imatinib has shown limited efficacy for treating Ph-positive acute lymphoblastic leukemia. In our study, we have investigated the effect of Imatinib therapy on murine P190 Bcr/Abl lymph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
41
1
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 47 publications
(55 reference statements)
4
41
1
1
Order By: Relevance
“…Recently, Mishra et al provided evidence that CXCL12 produced by stromal cells is responsible for protecting Bcr/Abl lymphoblasts from imatinib-induced cell death. 25 In contrast to our findings, they found that the protective effect is mediated by soluble CXCL12 produced by MSC and independent of direct contact of lymphoma cells with stroma. However, biological differences between lymphoblasts and CML progenitors may account for this discrepancy as protection mediated by cell contact between stroma and other leukemias has been previously reported.…”
Section: Discussioncontrasting
confidence: 99%
“…Recently, Mishra et al provided evidence that CXCL12 produced by stromal cells is responsible for protecting Bcr/Abl lymphoblasts from imatinib-induced cell death. 25 In contrast to our findings, they found that the protective effect is mediated by soluble CXCL12 produced by MSC and independent of direct contact of lymphoma cells with stroma. However, biological differences between lymphoblasts and CML progenitors may account for this discrepancy as protection mediated by cell contact between stroma and other leukemias has been previously reported.…”
Section: Discussioncontrasting
confidence: 99%
“…Although encouraging, these observations do not address the possibility that tumor environment may indirectly impact drug efficacy. For example, stromal-mediated protection of leukemia cells in bone marrow from the anticancer activity of tyrosine kinase inhibitors has been reported recently (44,45). Likewise, our data identify Hsp90-dependent, osteoclastmediated protection of certain solid tumors from Hsp90 inhibitors as a potentially important mechanism of chemoresistance that must be overcome to achieve the optimal clinical benefit of these highly promising molecularly targeted drugs.…”
Section: Discussionsupporting
confidence: 52%
“…BCR-ABL -expressing lymphoblasts (40). In our system, the prosurvival effects of MSC on imatinib-induced growth inhibition of KBM-5 cells were blocked by AMD3465, suggesting that the CXCR4 up-regulation induced by imatinib and bone marrow stroma promotes survival of CML cells.…”
Section: Discussionmentioning
confidence: 67%